The family council - Aguilar Llanos, Benjamín (2012)
One of the institutions of the Family Law with less presence in our courts, is precisely the Council of family; there are several reasons given for little application since the apparent demise of the compound and extended family, the regime way which the institution has been regulated, as well as its patrimonial vision; however,the institution was created to fulfill an important role within the context of the family,and we should aim to it. This work aims to develop the knowledge of the institution, its functions and objectives, all within the regulation which brings the Civil Code, and without making criticisms and recommendations for ensuring the effectiveness of the institution.